The girl with a mind for math : the story of Raye Montague - Mosca, Julia Finley (Mosca, Julia Finley. Amazing scientists, 2018)
This is a rhyming-text picture book about Raye Montague. After touring a German submarine in the early 1940s, young Raye set her sights on becoming an engineer. Little did she know sexism and racial inequality would challenge that dream every step of the way, even keeping her greatest career accomplishment a secret for decades. Through it all, the gifted mathematician persisted-- finally gaining her well-deserved title in history: a pioneer who changed the course of ship design forever.--Dust jacket.